Data and performativity in doctoral education: Information gaps and suggestions for overcoming them - Catalina Wainerman; Iván Matovich (Arizona State University, 2016)
Since the mid-1990s, there has been an abrupt growth of doctoral enrollments and doctoral programs in Argentina and Latin America. However, completion rates at this education level are far from satisfying. Attrition rates in  Social Sciences doctoral programs "are known" to be high, and higher in Social Sciences and Humanities (which will be later called "Soft Sciences") than in STEM (which will be later called "Hard Sciences") disciplines, although there are no valid and reliable data. In order to address this problem, we carried out an investigation with two objectives: (1) to measure performance (efficiency or productivity) in 18 doctoral programs in STEM disciplines, the Social Sciences, and Humanities at various universities in Buenos Aires city and the surrounding Metropolitan Area; and (2) to design a procedure for collecting valid and reliable information that would allow us to assess doctoral programs' performance. This measure was defined along two dimensions: completion rates (regular time rates and extra time rates) and average time-to-degree by cohort. We compiled data on individuals' academic tracks in each cohort from their enrollment to their completion or dropout by using paper-files and digitized databases provided by academic departments. Information was analyzed by program, by cohort, and by six grouped cohorts for 2001-2006. Substantive and methodological results were found. Among the substantive results, we discovered better performance in STEM disciplines than in the Social Sciences and Humanities. As to the methodological results, postgraduate statistical registering matrix was designed and a series of recommendations are presented for use by doctoral programs and graduate programs generally.